PERBANDINGAN HITUNGAN LUAS PADA SISTEM PROYEKSI TM 30 YANG DIGUNAKAN OLEH BADAN PERTANAHAN NASIONAL DENGAN SISTEM PROYEKSI UTM - Dea Mutiara Sundus, - (2011)
Map is a representation of part or all of the curved surface of the earth into a flat field. Badan Pertanahan Nasional (BPN) as a government agency that provides legal certainty to land ownership has adopted a standard National Mapping and produce maps of land registration map is accurate to digital projection system TM 3 with the WGS 84 reference ellipsoid. TM 3 and UTM projection are two types of transverse cylindrical projection conform. Geometrically the two systems have the same projection as the cylinder to cut the ball field of the earth on two meridians. The difference between TM 3 with projection projection UTM zone lies only in the width and scale factor at central meridian. The comparison that occurs in the use of the TM projection system 3 is used by the BPN with UTM projection system, through the software with multiple samples obtained from the PLA so as to provide a conclusion that there is no projection system that can actually maintain its original characteristics in the whole region/ zone , can do is try to get the distortion/ error that occurs as small as possible